2017
DOI: 10.12785/jtte/050103
|View full text |Cite
|
Sign up to set email alerts
|

Big Five Personality Traits influencing Secondary Students' Environmental Literacy in Ondo State, Nigeria

Abstract: Abstract:The human population growth and technological advancement have spurred radical changes in the global environments that are harmful. Unfortunately, scholars have continued to tackle these environmental problems without paying attention to the personality factors responsible for such phenomena. It is consequent on these that this study investigated the combined and independent effects of big five personality factors namely openness to experience, extraversion, agreeableness, conscientiousness, and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Although previous studies examined the relations between Big Five personality traits and components of GHC, such as environmental knowledge (Akomolafe, 2017), environmental concern (Hirsh, 2010), environmental engagement (Milfont & Sibley, 2012), and environmental attitude (Verma et al, 2017), our study is the first empirical work to explicitly explore the relations between Big Five personality traits and GHC. Regarding hypothesized paths that were supported in the Big Five personality domains, agreeableness and openness have positively significant impacts on GHC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although previous studies examined the relations between Big Five personality traits and components of GHC, such as environmental knowledge (Akomolafe, 2017), environmental concern (Hirsh, 2010), environmental engagement (Milfont & Sibley, 2012), and environmental attitude (Verma et al, 2017), our study is the first empirical work to explicitly explore the relations between Big Five personality traits and GHC. Regarding hypothesized paths that were supported in the Big Five personality domains, agreeableness and openness have positively significant impacts on GHC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research that randomly selected 462 secondary school students in Nigeria found that conscientiousness, extraversion, and agreeableness had a significant influence on environmental knowledge, whereas neuroticism and openness had no significant impact (Akomolafe, 2017). Another study conducted among German adults found that, among these five factors, agreeableness and openness are highly associated with environmental concern followed by neuroticism, conscientiousness, and extraversion (Hirsh, 2010).…”
Section: Big Five Personality and Ghcmentioning
confidence: 99%
See 3 more Smart Citations